Revealing organisational influence: conceptual and empirical reflections on doing inequality in digital work organisations - Vollmar, Leoni (Frontiers in Sociology, 2024)
The impact of digitalisation at work on existing inequalities is a growing concern. Social inequality is not solely determined by material circumstances, but also by the new social practises that arise in the workplace. However, the discourse about the digitalisation of work lacks specific organisational references. From an organisational theory perspective, it is important to note that digitality always takes place in an organisation-specific manner. Therefore, digitality and organisation are in a reciprocal relationship, resulting in the development of new organisational practises that impact organisational actors as structural conditions of organisational digitality. How the changes at the organisational level affect the mechanisms of production of social inequality in the course of digitalisation has not yet been taken into account, which means that previous research on inequality in digitalised work only allows an organisation-unspecific view of the subject. In contrast, this article places the organisation at the centre of the debate and presents a methodical approach for researching social inequality in the digitalisation of work from the perspective of organisational theory.